2012
DOI: 10.1186/1742-4933-9-20
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer disease and platelets: how’s that relevant

Abstract: Alzheimer Disease (AD) is the most common neurodegenerative disorder worldwide, and account for 60% to 70% of all cases of progressive cognitive impairment in elderly patients. At the microscopic level distinctive features of AD are neurons and synapses degeneration, together with extensive amounts of senile plaques and neurofibrillars tangles. The degenerative process probably starts 20–30 years before the clinical onset of the disease. Senile plaques are composed of a central core of amyloid β peptide, Aβ, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 139 publications
0
87
0
5
Order By: Relevance
“…Thus, it is necessary to consider the relationship between genetic risk factors and markers for AD pathology for future metabolomics, proteomics and imaging studies38. Moreover, many researchers have discussed evidence for underlying AD mechanisms, including an important relationship between resting state functional connectivity and the resulting distinctive pattern of Aβ plaque deposition in specific brain regions39404142. Thus, we should be able to predict the changes of metabolism in specific regions regarding the deposition of Aβ plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to consider the relationship between genetic risk factors and markers for AD pathology for future metabolomics, proteomics and imaging studies38. Moreover, many researchers have discussed evidence for underlying AD mechanisms, including an important relationship between resting state functional connectivity and the resulting distinctive pattern of Aβ plaque deposition in specific brain regions39404142. Thus, we should be able to predict the changes of metabolism in specific regions regarding the deposition of Aβ plaques.…”
Section: Discussionmentioning
confidence: 99%
“…APP is an integral membrane protein, made by neurons and other brain cells and is also expressed in extraneural tissues such as pancreas, kidney, and spleen and is abundant in blood platelets. 25 Its function is unknown. Neurotoxic APs are composed predominantly of amyloid-b (Ab) peptides of 40 (Abx-40) and 42 (Abx-42) amino acids in length, formed by sequential cleavage of APP by b-, and g-secretases.…”
Section: Neuropilar Lesionsmentioning
confidence: 99%
“…For decades, platelets have been considered a good model to study the pathophysiology of AD and a promising source of AD biomarkers, because platelets display all the enzymes of an amyloidogenic pathway and generate Aβ peptides ( Figure 1B) [19]. It has been suggested that full-length APP acts as a receptor on the platelet surface and also appears to be crucial in the regulation of intracellular Ca 2+ concentration [20].…”
Section: Prospective Ad Biomarkers In Plateletsmentioning
confidence: 99%